2006
DOI: 10.1071/ea06010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of stimulation on tenderness of lamb with a focus on protein degradation

Abstract: Abstract. Past studies have identified that electrical stimulation systems not only affect the pH-temperature decline of lamb carcasses, but also affect the tenderness of the product. It is unknown whether these differences are due to the effects of an optimal pH-temperature decline path by which the occurrence of shortening is decreased and proteolytic enzyme activity is increased, or by another mechanism, such as disruption of the muscle myofibres. This study attempted to elucidate this by placing control an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2008
2008
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 10 publications
0
6
0
1
Order By: Relevance
“…The literature is not clear on the effect of ES on MFI in lamb. Past studies did not report any effect of ES on MFI (Kerth et al 1999;Martin et al 2006;Toohey et al 2008), while other studies found higher MFI following ES (Kadim et al 2009;Abbasvali et al 2012). Differential response to ES between studies may have arisen from inherent experimental conditions.…”
Section: Cooking Loss and Tendernessmentioning
confidence: 92%
“…The literature is not clear on the effect of ES on MFI in lamb. Past studies did not report any effect of ES on MFI (Kerth et al 1999;Martin et al 2006;Toohey et al 2008), while other studies found higher MFI following ES (Kadim et al 2009;Abbasvali et al 2012). Differential response to ES between studies may have arisen from inherent experimental conditions.…”
Section: Cooking Loss and Tendernessmentioning
confidence: 92%
“…The MFI was higher in the treatment groups, the phenomenon that was previously addressed by Sonaiya and others (1982), Kerth and others (1999), and Martin and others (2006). MFI has been used as an indicator of PM proteolysis (Olson and others 1976; Lametsch and others 2007).…”
Section: Resultsmentioning
confidence: 76%
“…There were differences between the 5 times of ageing in MFI. The MFI increased in accordance to the ageing time (Sonaiya and others 1982; Martin and others 2006; Toohey and others 2008). The highest MFI was observed in the 5th treatment group, indicating that higher voltage/duration of ES was more effective on the MFI.…”
Section: Resultsmentioning
confidence: 87%
“…When comparing the effect size of subgroups, ES meat aged for 1-3 days showed the greatest reduction in WBSF (−0.78) as compared with the other subgroups. Most of the studies in the database have reported a reduction in WBSF in meat subjected to ES followed by meat ageing [1,[32][33][34]50], although in approximately half the comparisons, the effects were statistically insignificant (Figure 1). Thus, using the statistical power of a meta-analysis, we demonstrated that ES was effective for improving tenderness of small ruminant meat.…”
Section: Effect On Warner-bratzler Shear Force (Wbsf)mentioning
confidence: 99%